Taenia solium cysticercosis [ from basic to clinical science - Prabhakar, S. [ (Sudesh)]; Singh, G. [ (Gagandeep)] (New York : CABI, 2002)
Taenia solium cysticerosis is a parasitic disease caused by the dissemination of the larval form of the pork tapeworm. This book covers basic science, epidemiology, clinical aspects, pathology, investigational aspects of neurocysticercosis and therapy ad prevention.
Taenia solium cysticercosis : basic science -- 2. Epidemiologi -- 3. Taenia solium cysticercosis : clinical aspects -- 4. Cysticercosis : pathology -- 5. Neurocysticercosis : investigational aspects -- 6. Taeniasis-cysticercosis : therapy and prevention
Includes bibliographical references and index
Keywords: Cysticercosis; Taenia